Multifactor analysis of urban pluvial flooding using a comprehensive vulnerability index - Eka Mutia; Azmeri Azmeri; Alfiansyah Yulianur; Ashfa Achmad; Ella Meilianda (Jàmbá)
Urbanity is facing a growing threat of pluvial flooding due to rampant urbanisation and transformations combined with insufficient drainage systems. This situation becomes aggravated by flat topography and heavy rainfall, especially in poorly drained areas. Assessing flood vulnerability at the community level using the Flood Vulnerability Index (FVI) is essential for effective urban planning and flood risk management. The FVI consists of four key components: physical, environmental, social and economic. Physical factors encompass topography, rainfall and drainage systems, while environmental factors involve green spaces and retention zones. Social factors pertain to population density and community awareness, whereas economic factors relate to potential revenue losses and recovery capacity. The FVI was calculated using both secondary data and field observations, based on exposure, sensitivity and adaptive capacity. High population density, low green area ratio and poor drainage conditions are associated with high FVI, while when accompanied by higher environmental support and adaptive capacity in the community, lower vulnerability was observed.